Performance Improvement Strategy for Banjar City Election Commission Employees - Geri Garyadina Mauluddin; Eko Hariyanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The implementation of KPU programs and activities as a hierarchical part of the KPU in the context of implementing functions and achieving performance is financed by the State Budget (APBN) and the Regional Budget (APBD). The purpose of this research is to analyze the performance improvement strategy of Banjar City KPU employees. This study uses a qualitative approach and collects data through in-depth interviews with 7 respondents who know about the KPU's performance in the city of Banjar. Data analysis was carried out through translation, and the expected conclusions were obtained. The findings show that in improving the performance of KPU staff, they coordinate with election monitoring agencies, local governments, and involve staff in staff training.